Maximally star-forming galactic disks II.: vertically resolved hydrodynamic simulations of starburst regulation - Shetty, Rahul; Ostriker, Eve C. (The astrophysical journal, 2012)
We explore the self-regulation of star formation using a large suite of high resolution hydrodynamic simulations, focusing on molecule-dominated regions (galactic centers and [U]LIRGS) where feedback from star formation drives highly supersonic turbulence. In equilibrium the total midplane pressure, dominated by turbulence, must balance the vertical weight of the ISM. Under self-regulation, the momentum flux injected by feedback evolves until it matches the vertical weight. We test this flux balance in simulations spanning a range of parameters, including surface density $Σ$, momentum injected per stellar mass formed (